1997
DOI: 10.1007/s007050050063
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the expression of endothelial cell integrin receptors α5β1 and α2β1 and α6β1 after in vitro infection with a clinical isolate of human cytomegalovirus

Abstract: Human cytomegalovirus infection of human umbilical vein endothelial cells reduces the ability of these cells to bind to fibronectin, collagen type IV and laminin. This suppression requires active virus, since UV-inactivated virus did not alter the binding ability of these cells to adhere to fibronectin, collagen type IV, and laminin. In an attempt to elucidate the molecular mechanism of this altered interaction, the surface expression of alpha 5 beta 1, alpha 2 beta 1, alpha 3 beta 1, and alpha 6 beta 1 integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
0
20
0
2
Order By: Relevance
“…HCMV infection also alters cell cycle regulation (27,53,54), cell adhesion molecule (76) and transcription factor expression and activities (36), and influences genes that can be involved in oncogenesis (7). Each of the two clusters of host genes that responded to HCMV infection in the present study included genes encoding proteins that participate in each of these processes, which we discuss below.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…HCMV infection also alters cell cycle regulation (27,53,54), cell adhesion molecule (76) and transcription factor expression and activities (36), and influences genes that can be involved in oncogenesis (7). Each of the two clusters of host genes that responded to HCMV infection in the present study included genes encoding proteins that participate in each of these processes, which we discuss below.…”
Section: Discussionmentioning
confidence: 95%
“…By negatively impacting these cellular functions in the immune system, decreased expression of adhesion molecules in response to HCMV infection would severely compromise the host response to the infection. Several studies support this idea; for example, HCMV infection of human endothelial cells (76) and human fibroblasts (93) altered the expression of the integrin ␤1-subunit. Another report showed that integrin activation of cyclin-dependent kinases 2 and 6 was necessary for cells to progress through G 1 of the cell cycle and also for the expression of cyclin D1 (24).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, integrin molecules, especially ␤1-and ␣ v -integrin subunits, were down-regulated from the surfaces of several, but not all, cell types by Ebola virus GP. Several viruses, including human CMV, down-regulate or bind to integrin subunits and can induce cell rounding and detachment (37). Moreover, similar effects can be induced by antibodies to ␤1-integrin (30).…”
Section: Discussionmentioning
confidence: 99%
“…The ␣2␤1, ␣V␤3, and ␣6␤1 integrins are important human cytomegalovirus receptors (23). Human cytomegalovirus infection has been shown to down-regulate ␣2␤1 and ␣5␤1 but upregulate ␣6␤1 on endothelial cells, down-regulate ␣1␤1 on fibroblasts, and up-regulate ␤1 integrins on monocytes and prostate tumor cells to facilitate motility (8,60,63,68). Nonpathogenic and pathogenic hantaviruses use ␤1 and ␤3 integrins, respectively, for endothelial cell entry.…”
mentioning
confidence: 99%